IDENTIFIKASI MISKONSEPSI SISWA PADA MATERI RANGKAIAN ARUS BOLAK-BALIK MENGGUNAKAN FOUR-TIER TEST DI SMA - Reni Dias Agustin; Alex Harijanto; Sri Handono Budi Prastowo (JURNAL PEMBELAJARAN FISIKA, 2018)
ABSTRACT The purpose of this study was to describe the students’ misconceptionsin alternating current circuit in the twelfth grade of Senior High School. Thiskind of research was descriptive research. The research population was allstudents of twelfth grade in Senior High School B. The samples of the researchwere the students of class Science X, Science Y, and Science Z. Data collectionmethod used in this research was test and documentation. The test instrumentthat used was a four-tier test. The result showed that students of Senior HighSchool B had misconception in alternating current circuit with the percentageof 40.3% and it was categorized very low. Keywords: Misconception, Four-Tier Diagnostic Test, Alternating Current Circuit